2008
DOI: 10.1016/j.jvs.2008.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcome predictors for lower extremity atherectomy procedures

Abstract: Lower extremity atherectomy procedures with the SilverHawk device are safe and effective means in improving symptoms. However, there is decreased durability and significant patency and limb loss over time. Diabetes, renal disease, tobacco use, and tissue loss are all associated with inferior outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…This study showed 12‐month primary and secondary patency of 66 and 70%, respectively, and reported a 10‐fold increase in restenosis rates if the vessels were undergoing re‐intervention. Sarac et al . recorded primary and secondary patencies of 43 and 57% at 12 months; however, 58% of the cohort in this study had tissue loss, implying a more severely diseased cohort than those in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…This study showed 12‐month primary and secondary patency of 66 and 70%, respectively, and reported a 10‐fold increase in restenosis rates if the vessels were undergoing re‐intervention. Sarac et al . recorded primary and secondary patencies of 43 and 57% at 12 months; however, 58% of the cohort in this study had tissue loss, implying a more severely diseased cohort than those in our study.…”
Section: Discussioncontrasting
confidence: 74%
“…These new techniques are not readily available, however, and have their own limitations and uncertainties. 17,18 Another limitation is that coronary interventions and procedures done in other facilities were not included in this report. The cumulative level of radiation exposure would be higher if these were included.…”
Section: Discussionmentioning
confidence: 99%
“…Sarac et al recruited 167 patients treated with Silver Hawk device in tibial arteries. Cumulative 1-year primary and secondary patency rates were 43% and 57%, respectively [45]. An interesting result comes from Shammas et al trial which demonstrates the inferiority of Silver Hawk atherectomy versus balloon angioplasty.…”
Section: Introductionmentioning
confidence: 99%